The influence of comfort food on health: A review (Research, Society and Development, 2022)
Objective: to discuss the influence of comfort food on people's health, demonstrating the consequences of this type of food. Methodology: narrative review of the literature carried out on studies published in national and international journals through a bibliographic search of articles in English and Portuguese, available in the following databases: Scielo, Google academic and PubMed. The descriptors used were: “Comfort food and nutrition”, “Characteristics of comfort food”, “Culture and food” and “Types of comfort food”. Results: Comfort food is the product of a behavior influenced by cultural, socioeconomic, gender and age characteristics, that is, the subject's personal history. The different types of comfort food are capable of awakening human emotional connections with the past, as well as relieving periods of stress and anxiety. Final considerations: comfort food does not have evidence and nutritional bases to draw general profiles, thus being totally subjective from person to person. It was possible, however, to conclude that comfort food can cause well-being, which is undoubtedly one of the main benefits that affective foods can provide. But, on the other hand, the imbalance and the frequent search for the sensation of comfort food can cause harm to physical and mental health, which can lead to binge eating and obesity as a consequence.